NKCC1 and KCC2: Structural insights into phospho-regulation - Hartmann, Anna-Maria; Nothwang, Hans Gerd (Frontiers in Molecular Neuroscience, 2022)
Inhibitory neurotransmission plays a fundamental role in the central nervous system, with about 30-50% of synaptic connections being inhibitory. The action of both inhibitory neurotransmitter, gamma-aminobutyric-acid (GABA) and glycine, mainly relies on the intracellular Cl- concentration in neurons. This is set by the interplay of the cation chloride cotransporters NKCC1 (Na+, K+, Cl- cotransporter), a main Cl- uptake transporter, and KCC2 (K+, Cl- cotransporter), the principle Cl- extruder in neurons. Accordingly, their dysfunction is associated with severe neurological, psychiatric, and neurodegenerative disorders. This has triggered great interest in understanding their regulation, with a strong focus on phosphorylation. Recent structural data by cryogenic electron microscopy provide the unique possibility to gain insight into the action of these phosphorylations. Interestingly, in KCC2, six out of ten (60%) known regulatory phospho-sites reside within a region of 134 amino acid residues (12% of the total residues) between helices α8 and α9 that lacks fixed or ordered three-dimensional structures. It thus represents a so-called intrinsically disordered region. Two further phospho-sites, Tyr903 and Thr906, are also located in a disordered region between the ß8 strand and the α8 helix. We make the case that especially the disordered region between helices α8 and α9 acts as a platform to integrate different signalling pathways and simultaneously constitute a flexible, highly dynamic linker that can survey a wide variety of distinct conformations. As each conformation can have distinct binding affinities and specificity properties, this enables regulation of [Cl-]i and thus the ionic driving force in a history-dependent way. This region might thus act as a molecular processor underlying the well described phenomenon of ionic plasticity that has been ascribed to inhibitory neurotransmission. Finally, it might explain the stunning long-range effects of mutations on phospho-sites in KCC2.